2018
DOI: 10.4103/0366-6999.238152
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Human Immunodeficiency Virus Infection at Diagnosis among New Human Immunodeficiency Virus Cases in Dehong, Yunnan, China, 2008–2015

Abstract: Background:On diagnosis of human immunodeficiency virus (HIV) infection, a person may have been infected already for many years. This study aimed to estimate the duration of HIV infection at the time of diagnosis.Methods:Newly diagnosed HIV cases in Dehong, China, from 2008 to 2015 were studied. Duration of infection at the time of diagnosis was calculated using the first CD4 cell count result after diagnosis and a CD4 depletion model of disease progression. Multiple linear regression analysis was used to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…[ 14 , 15 ] One recent study reported that the mean duration of infection at the time of diagnosis for nearly 6000 Chinese PLWH newly diagnosed between 2008 and 2015 was 6.3 years. [ 16 ] Another new study reported that among >45,000 PLWH newly diagnosed between 2012 and 2016, 70% presented late and 45% had advanced HIV disease. [ 17 ] Earlier case finding and rapid diagnosis depends heavily on both the availability of quality testing services in a variety of formats and on the uptake of testing services by those who need them.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 , 15 ] One recent study reported that the mean duration of infection at the time of diagnosis for nearly 6000 Chinese PLWH newly diagnosed between 2008 and 2015 was 6.3 years. [ 16 ] Another new study reported that among >45,000 PLWH newly diagnosed between 2012 and 2016, 70% presented late and 45% had advanced HIV disease. [ 17 ] Earlier case finding and rapid diagnosis depends heavily on both the availability of quality testing services in a variety of formats and on the uptake of testing services by those who need them.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PLWH often have already had HIV infection for some years at the time of diagnosis. Indeed, a recent study in China found a median duration of infection of 6.3 years before diagnosis [20]. This means that, in China, an individual with CD4 cell counts consistently ≥500/μL without ART for >8 years, has probably been infected for even longer and remained “healthy.” Moreover, it was common during our study period for persons with newly diagnosed HIV with CD4 cell counts above the 200/μL, 350/μL, and 500/μL thresholds to remain untreated for some time [21].…”
Section: Methodsmentioning
confidence: 99%
“…Most definitions captured in the review by Gurdasani et al [5] used a 10-year nonprogression period and a CD4 cell count threshold of 500/μL. Therefore, we too selected the ≥500/μL threshold but chose a somewhat shorter ≥8-year nonprogression period for our study, because HIV in China is often diagnosed late, a median of 6.3 years after infection [20].…”
Section: Methodsmentioning
confidence: 99%
“…This is especially true when one considers the persistent problem of late diagnosis in China. A recent study estimated that newly diagnosed PLWH in China had already had HIV infection for a mean of 6.3 years at the time of their diagnosis [ 29 ]. Thus, in the China setting, after many years scaling up HIV testing, new diagnoses are still not the same thing as new infections.…”
Section: How Much Transmission Is Occurring?mentioning
confidence: 99%
“…However, in China at least, this assumption is clearly incorrect. Although these figures likely reflect the troubling problem of late diagnosis in China [ 29 ], they may also suggest a rise in the use of erectile dysfunction medication (EDM) or their less expensive alternatives, which in China are typically unregulated, illegally manufactured aphrodisiacs of unknown chemical composition. Studies among older Chinese men have suggested that EDM or aphrodisiac use, especially among those engaged in low-cost commercial sex and/or condomless sex, have greater risk of HIV and other sexually transmitted infections [ 36 , 37 ].…”
Section: In What Contexts Is Transmission Occurring?mentioning
confidence: 99%